The European Crisis and Global Economy Dynamics: Continental Enlargement versus Atlantic Opening - Mendonça, António (Panoeconomicus, 2014)
The fundamental idea we discuss in this paper is that the failure of Europe to deal with the international crisis is due, first and foremost, to the deepening of a more specific crisis that affected the very process of European integration and developed through two main channels: one, broader, linked to the erosion of the original driving forces underpinning integration in Europe; another, more circumscribed, linked to the malfunctioning of the euro as an internal adjustment mechanism of the currency zone. To deal with these structural dimensions of the crisis, we put forward a model of a Global Europe against the model of Continental Europe that has dominated the integration process until now and in this alternative framework we discuss the potential role of Portugal and of the Community of Portuguese Speaking Countries. Key words: Economic crisis, Euro crisis, Economic integration, Globalization, Community of Portuguese speaking countries. JEL: F15, F40, F50.